Experimental investigation on melting heat transfer of paraffin wax-Al2O3 storage system - Hamdani; Thaib R.; Irwansyah; Dailami; Mahlia T.M.I. (Research India Publications, 2023)
Background: A systems ofLatent Heat Thermal Energy Storage (LHTES) based on paraffin wax (n-octadecane/C18 H18) have low heat transfer rates during either melting or freezing processes. To enhance paraffin wax thermal conductivity, alumina (Al2O3) as a material which high conductivity was employed. Parafin wax was dispersed with alumina homogenously with volume fraction 2%, 4%, 6%, 8% and 10%.Objective: This paper examines the thermal conductivity enhancement using paraffin wax as a heat storage material by mixed with alumina (Al2O3) particles.Results:At starting heat, paraffin wax absorbs sensible heat and then latent heat which takes place at a temperature nearly constant. Similarly, at the beginning of the heating process, temperature increases rapidly until paraffin reach its melting temperature and tend to increased constantly after the temperature reached 60°C. Conclusion: The addition of Al2O3 particles which have a high thermal conductivity could able to increase thermal conductivity of paraffin wax as a heat storage media. Adding amount of Al2O3 particles will reduce latent heat thermal of energy storage material. The conduction heat transfers dominantly during melting and freezing processes. Alumina particles is play significantly in the solidification process comparing to melting process. During freezing process, solid layer was formed on top surface of heat exchanger and remain stable. It can be concluded that by adding alumina particles could increase heat exctraction during solidification process. As a results, it produces low latent heat and high thermal conductivity. © Research India Publications.